Wildlife Crime and Prosecution Effectiveness in the State of Uttarakhand - Mehra, Surender; Gupta, Sandeep Kumar (Indian Forester, 2025)
The authors present the analysis of wildlife offense records for the state of Uttarakhand with especial reference to the frequent victim species and prosecution success. Based on data collected from different forest divisions and police departments they observed variable duration of investigations. Of the 563 wildlife offence cases, 471 were reported by forest department and 92 by Police department of Uttarakhand. Among 333(54%) cases were of Schedule-I, 12(2%) were of Schedule-II, 161 (26%) were of Schedules-III and 11(2%) were of Schedule-IV species under the Wild Life (Protection) Act, 1972. It was also observed that 66 (11%) wildlife samples were inconclusive, 14(2%) unscheduled and 8(1%) were found to be fake and remaining 8(1%) cases are still pending with wildlife forensics lab, WII, Dehradun in Uttarakhand, conviction rate in respect of arrested offenders was 50%. In Rajaji Tiger Reserve, only 10 offenders were convicted out of 80 got arrested. In cases of police department only 4 offenders got convicted out of 86 being arrested in wildlife seizure cases. The Kumaon zone has demonstrated a stronger performance in wildlife prosecution, where 66 out of 79 cases have resulted in convictions. The wildlife zone demonstrated robust conviction record, where 60 out of the 162 registered wildlife cases have been decided by trial courts with favourable outcomes for the prosecution in 52 cases. The presented data will be useful in understanding the gaps in law enforcement and streamlining the follow-up mechanism in the logical conclusion of the associated cases.